Pre T-Cell Receptor Alpha (pTα) Expression Patterns and Functional Analysis in Human T-Cell Lymphoblastic Leukemia - Philipp Ivanyi; Michael Morgan; Wenji Piao; Sya N. Ukena; Klaus Steube; Arnold Ganser; Anke Franzke (Cellular Oncology)
Background: The pTα/preTCR regulates the β-selection, a crucial T-cell developmental checkpoint, providing a most potent survival advantage to thymocytes mediated by the src-kinase p56Lck.